2010
DOI: 10.3758/mc.38.5.617
|View full text |Cite
|
Sign up to set email alerts
|

The role of inhibition in the production of disfluencies

Abstract: Disfluency is a common occurrence in speech and is generally thought to be related to difficulty in the production system. One unexplored issue is the extent to which inhibition is required to prevent incorrect speech plans from being articulated. Therefore, we examined disfluency production in participants with attentiondeficit/ hyperactivity disorder (ADHD), which is linked to deficits in inhibitory function and response suppression (Nigg, 2001). Participants completed a sentence production task in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 70 publications
8
49
2
1
Order By: Relevance
“…Ellis and Yuan, 2005). The direct relation between syntactic complexity and utterance fluency, however, has thus far only been investigated in native speaker performance (Engelhardt et al, 2010). The current short research article compares the effect of syntactic complexity in first language (L1) and L2 speaking fluency, in answering the following research question:…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Ellis and Yuan, 2005). The direct relation between syntactic complexity and utterance fluency, however, has thus far only been investigated in native speaker performance (Engelhardt et al, 2010). The current short research article compares the effect of syntactic complexity in first language (L1) and L2 speaking fluency, in answering the following research question:…”
Section: The Current Studymentioning
confidence: 99%
“…They also measured formulation times and report that passives are formulated slower than actives. Engelhardt et al (2010) measured how participants' fluency was affected by producing passives versus actives, much like the current study will do. They compared the speech production of healthy and attention deficit/hyperactivity disorder (ADHD) native English participants, with the goal of investigating the role of inhibition in the production of disfluencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, evidence suggests that brain-damaged patients with deficient inhibiting abilities have difficulty producing words under conditions of high lexical competition in a word generation task (e.g., Badre, Poldrack, Paré-Blagoev, Insler, & Wagner, 2005;Thompson-Schill et al, 1998). Studies of ADHD have indicated that deficient inhibiting abilities caused disfluencies during sentence production (e.g., Engelhardt, Corley, Nigg, & Ferreira, 2010). In the ageing literature, age-related declining inhibiting abilities have been associated with increased lexical competition effects in both spoken word recognition and production (e.g., Taler, Aaron, Steinmetz, & Pisoni, 2010).…”
mentioning
confidence: 99%
“…Pausing and speed have been shown to be relatively good markers of (dis)fluency (Bosker et al, 2013;De Jong et al, 2015;Freed, 2000;Kahng, 2014). On the other hand, the repairs (false starts, repetitions, replacements, and reformulations) have been studied to a much lesser extent, and their relationship to L2 proficiency has been questioned (Engelhardt et al, 2010;Gilabert, 2007;Kormos, 1999;Lennon, 1990). These results have important implications for the current study as well, when considering the different types of disfluencies (inaccuracies) and proficiency.…”
Section: Defining and Measuring Fluencymentioning
confidence: 71%
“…Second language (L2) fluency has received growing interest in recent years (e.g., Akamatsu, 2008;Bosker, Pinget, Quené, Sanders & De Jong, 2013;De Jong, Groenhout, Schoonen & Hulstijn, 2015;Engelhardt, Corley, Nigg & Ferreira, 2010;Housen & Kuiken, 2009;Kahng, 2014;Kame'enui & Simmons, 2001;Riggenbach, 2000;Segalowitz, 2010;Snellings, Van Gelderen & De Glopper, 2002). No clear consensus has been reached, though, on what is meant by fluency of language use.…”
Section: Introductionmentioning
confidence: 99%